Simulation and Experimentation of Sawtooth Wave Generation using Diode-Capacitor Pair - Mallick, A.; Guin, P.; Roy, A. (Journal of Scientific Research, 2022)
A simple, inexpensive and efficient circuit for generating sawtooth waves is demonstrated in this paper. The novelty of this work lies in the fact that the voltage of a charging capacitor provides linear response when it is charged through a reverse-biased diode. A rectangular wave of extremely high duty cycle is used as a reference signal to drive the passive circuit consists of a diode–capacitor pair. During the on-time of the reference signal, the diode remains in reverse biased condition while charging the capacitor and during charging through the reverse-biased diode, the capacitor voltage produces the required ramp. During the off-time of the reference wave, the diode becomes forward biased and the capacitor discharges very fast through the forward-biased diode and thus a sawtooth wave has resulted. At high frequencies, the parasitic depletion capacitance of the diode cannot be ignored and it limits the frequency of operation. Laboratory experiments, as well as PSPICE circuit simulations, are performed to established our idea of generating sawtooth waveforms. The experiment is found to be repetitive and robust.